2016
DOI: 10.1038/ncomms12625
|View full text |Cite
|
Sign up to set email alerts
|

On the complex structural diffusion of proton holes in nanoconfined alkaline solutions within slit pores

Abstract: The hydroxide anion OH−(aq) in homogeneous bulk water, that is, the solvated proton hole, is known to feature peculiar properties compared with excess protons solvated therein. In this work, it is disclosed that nanoconfinement of such alkaline aqueous solutions strongly affects the key structural and dynamical properties of OH−(aq) compared with the bulk limit. The combined effect of the preferred hypercoordinated solvation pattern of OH−(aq), its preferred perpendicular orientation relative to the confining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(75 citation statements)
references
References 52 publications
2
73
0
Order By: Relevance
“…One sometimes uses a different perspective, namely that proton “holes”, i.e. , missing protons, are transferred from the hydroxide ion to the water molecule 2,3. The Grotthuss mechanism then becomes a series of proton hole transfer events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One sometimes uses a different perspective, namely that proton “holes”, i.e. , missing protons, are transferred from the hydroxide ion to the water molecule 2,3. The Grotthuss mechanism then becomes a series of proton hole transfer events.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, recent molecular dynamics (MD) studies10,11 have shown that OH – diffuses both vehicularly (mass transport) and via a Grotthuss-like mechanism in anion exchange membranes. Further, Muñoz-Santiburcio and Marx3 explored OH – diffusion in nanoconfined slit pores, and concluded that the transport mechanism depends on the degree of confinement. Achtyl et al 12 showed that protons can diffuse through hydroxyl-terminated atomic defects in single-layer graphene.…”
Section: Introductionmentioning
confidence: 99%
“…Another consequence attributed to a confined environment is its effect on the dielectric constant of interfacial water in comparison to bulk water, where charged species are stabilized to a greater extent at the interfacial region in comparison to bulk-water [ 46 ]. This conforms to Davis’ principle- the importance of being charged [ 34 ], observed at a lower confinement scale.…”
Section: Anomalous Water Properties In Confined Environmentsmentioning
confidence: 99%
“…Another interesting aspect of confined water is the efficient proton transfer at extreme confinement (by the Grotthuss mechanism) by retaining this property from bulk water [ 46 , 48 ]. Such efficient proton transfer in confinement might have preceded the efficient proton channels that are observed in contemporary cells and maintain a natural proton gradient.…”
Section: Anomalous Water Properties In Confined Environmentsmentioning
confidence: 99%
See 1 more Smart Citation